Gestational stress and fluoxetine treatment differentially affect plasticity, methylation and serotonin levels in the PFC and hippocampus of rat dams - Gemmel, M.; Rayen, I.; van Donkelaar, E.; Loftus, T.; Steinbusch, H. W.; Kokras, N; Dalla, C; Pawluski, J. L. (Neuroscience, 2016)
Women are more likely to develop depression during childbearing years with up to 20% of women suffering from depression during pregnancy and in the postpartum period. Increased prevalence of depression during the perinatal period has resulted in frequent selective serotonin reuptake inhibitor (SSRI) antidepressant treatment; however the effects of such medications on the maternal brain remain limited. Therefore, the aim of the present study is to investigate the effects of the SSRI medication, fluoxetine, on neurobiological differences in the maternal brain. To model aspects of maternal depression, gestational stress was used. Sprague-Dawley rat dams were exposed to either gestational stress and/or fluoxetine (5mg/kg/day) to form the following four groups: 1. Control+Vehicle, 2. Stress+Vehicle, 3. Control+Fluoxetine, and 4. Stress+Fluoxetine. At weaning maternal brains were collected. Main findings show that gestational stress alone increased synaptophysin and serotonin metabolism in the cingulate cortex2 region of the cortex while fluoxetine treatment after stress normalized these effects. In the hippocampus, fluoxetine treatment, regardless of gestational stress exposure, decreased both global measures of methylation in the dentate gyrus, as measured by Dnmt3a immunoreactivity, as well as serotonin metabolism. No further changes in synaptophysin, PSD-95, or Dnmt3a immunoreactivity were seen in the cortical or hippocampal areas investigated. These findings show that gestational stress and SSRI medication affect the neurobiology of the maternal brain in a region-specific manner. This work adds to a much needed area of research aimed at understanding neurobiological changes associated with maternal depression and the role of SSRI treatment in altering these changes in the female brain.
Keywords: Animals; antidepressant medication; Antidepressive Agents/pharmacology; Brain/*drug effects/metabolism; Depression/drug therapy; Depressive Disorder/drug therapy; Female; Fluoxetine/*pharmacology; Hippocampus/*drug effects/metabolism; Methylation; Neuronal Plasticity/*drug effects; Neuroplasticity; neurotransmitters; Postpartum depression; Pregnancy; Prenatal Exposure Delayed Effects/*drug therapy/metabolism; Rats, Sprague-Dawley; Selective Serotonin Reuptake Inhibitors/*pharmacology; Serotonin/*metabolism; Ssri; Stress, Physiological